Citizens' Satisfaction With Non-Cash Food Assistance - Ayu Pramestidewi, Chandra; Ismartaya, Ismartaya; Yulianingsih, Yulianingsih; Prio Utomo, Yoyok; Palahudin, Palahudin (Publisher Cv. Inara, 2023)
This observation will analyze the level of community satisfaction with non-cash food assistance for social services in the Cibinong District area, Bogor Regency, West Java. Since the March 2020 Pandemic, the government through the Social Service has collaborated with banks (Association of State Banks) to distribute non-cash food assistance (BPNT). Assistance is channeled by distributing electronic cards such as red and white special ATMs to prosperous families from the bank to underprivileged residents who have been registered in the Bogor Regency Social Service data. Then the card is exchanged for necessities (nine staples), namely: 10 kg of rice, 1 kg of eggs, 1 chicken meat, 0.5 kg of vegetables/fruit, and 250 grams of green beans, exchanged for e-Warung which has been provided by the Social Service Bogor Regency. Data collection through questionnaires and observation of e-Warung 40 respondents was taken based on a purposive random sampling technique. The data was analyzed through validity and reliability tests, as well as a hypothesis test in measuring the level of satisfaction of residents with BPNT through e-Warung in Cibinong. The results of the study provide clues that several dimensions of the level of satisfaction that affect the distribution of current BPNT in the Cibinong sub-district, namely: Accuracy in implementation, there are 6 precise aspects: Target, quantity, price, time, quality, and administration. There are two kinds of measurements of Family Welfare Nationally, namely, Measurements by the Central Bureau of Statistics and Measurements carried out by the National Family Planning Coordinating Board, with concerning e-Warung, measurements based on population, health, consumption patterns, and employment. The conclusion is that the level of citizen satisfaction with BPNT has a very positive effect. The results of the study stated that citizen satisfaction increased by 24% on the accuracy of providing assistance and satisfaction increased by 27% on e-Warung performance.